2022
DOI: 10.1111/ppc.13033
|View full text |Cite
|
Sign up to set email alerts
|

The effects of motherhood and body perception on sexual dysfunctions among pregnant women

Abstract: Purpose This study aimed to determine the effects of motherhood and body perception of pregnant women on sexual dysfunction. Methods Data were collected using a demographic data form, the Self‐Perception of Pregnants Scale (SPPS) and the Female Sexual Function Index (FSFI). The study which is cross‐sectional was conducted with 280 pregnant women. Percentages, Pearson correlation, and multiple regression analyzes were used for data analysis. Findings Pregnant women with a positive pregnancy‐related motherhood a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Gümüşay found that the positive body image of pregnant women had a positive effect on the sexual function of couples 7 . In another study, it was determined that positive body image during pregnancy was associated with lower sexual dysfunction 20 . As a result, physical or mental changes affect the sexual life during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Gümüşay found that the positive body image of pregnant women had a positive effect on the sexual function of couples 7 . In another study, it was determined that positive body image during pregnancy was associated with lower sexual dysfunction 20 . As a result, physical or mental changes affect the sexual life during pregnancy.…”
Section: Discussionmentioning
confidence: 99%